Ukrainian Metallurgy at the Global Market: Problems and Priorities - Vlasiuk, T. O. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
The status and potential of Ukrainian metallurgy at the global market are analyzed. The performance and capacities of the domestic metal industry, its foreign trade, the structure of exports and imports (including export destination) for 2008–2015 are overviewed. The key domestic manufacturers of industry for 2014–2015 market are analyzed. Estimation of global economic conjuncture change effects for the domestic metal industry is conducted. There is estimated that the main global competitors for Ukrainian steel companies are Chinese and Russian steel manufacturers. Key problems of the domestic metal industry are studied: (i) technical and technological backwardness, low cost effectiveness due to high rates of energy and resource consumption; shortage of resources; (iii) underdeveloped intra-industry and cross-industry coopera- tion; (iv) lack of regular government support for the industry and imperfect mechanisms for protection of domestic metal manufacturers; (v) ruined production facilities due to warfare in the Donbas region (where major metal industry facilities are concentrated). The analysis allows for formulating political priorities for the development of Ukrai- nian metal industry: stabilization and expansion of market segments for traditional and high tech products of metal industry, diversification of the industry markets; strengthening of the government’s role in import substitution, to balance the domestic demand for metal products with the output of the domestic metal industry; elaboration of government programs for the development of metal industry and related economic sectors; organization of regular cooperation with international institutions of industry development; investigation of anti- competitive behaviors at the steel market; adoption of a package of laws to stimulate the development of steel industry; improvement of the marketing infrastructure in the industry by creating a virtual marketplace for companies and systems for monitoring and forecasting of the domestic market; launch of investment projects on constructing compact factories based on innovative technologies.